A Scientific Investigation of Factors Related to Breast Milk Adequacy in Banjar Regency, South Kalimantan, Indonesia - Rusmilawaty; Tri Tunggal; Hapisah; Norlaila Sofia; Zulfikar Ali As (Postgraduate, University of Mataram, 2025)
Various maternal factors potentially influence breast milk sufficiency. This study aims to analyze maternal factors associated with breast milk sufficiency in Banjar Regency. This analytical study used a cross-sectional design and was conducted from April to July 2025 in the Banjar Regency Community Health Center. A total of 70 postpartum mothers were selected using a probability sampling method. The dependent variable was breast milk adequacy, while the independent variables included maternal age, gestational age, parity, psychological condition, sociocultural factors, breast and nipple condition, delivery method, contraceptive use, and early initiation of breastfeeding (IMD). Data were analyzed using the chi-square test and logistic regression. Bivariate analysis showed that nipple condition (p = 0.01; OR = 5.25), maternal age (p = 0.011; OR = 4.92), vaginal delivery (p = 0.03; OR = 2.89), and early initiation of breastfeeding (p = 0.039; OR = 2.89) were significantly associated with breast milk adequacy. Multivariate logistic regression confirmed that nipple condition was the most dominant factor (p = 0.04; AOR = 0.15; 95% CI: 0.02–0.99). The regression model showed good predictive power (R² = 0.61; classification accuracy = 82.90%). In conclusion, nipple condition is the most influential maternal factor in determining breast milk adequacy. These findings underscore the importance of early assessment of nipple anatomy and appropriate supportive interventions during pregnancy.